Annual report 1943-1944 - Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, 2020)
This report for the fiscal year 1943-44 is the second anual report rendered by the Institute to the Board of directors. It includes: a convention, a contructions program, experimental Works, educational program, and plans for future.